Borate Hydrides as a New Material Class: Structure, Computational Studies, and Spectroscopic Investigations on Sr5(BO3)3H and Sr5(11BO3)3D. Issue 51 (17th August 2020) - Wylezich, Thomas; Valois, Renaud; Suta, Markus; Mutschke, Alexander; Ritter, Clemens; Meijerink, Andries; Karttunen, Antti J.; Kunkel, Nathalie
Abstract: The unprecedented borate hydride Sr5 (BO3 )3 H and deuteride Sr5 ( 11 BO3 )3 D crystallizing in an apatite‐related structure are reported. Despite the presence of hydride anions, the compound decomposes only slowly in air. Doped with Eu 2+, it shows broad‐band orange‐red emission under violet excitation owing to the 4f 6 5d–4f 7 transition of Eu 2+ . The observed 1 H NMR chemical shift is in good agreement with previously reported 1 H chemical shifts of ionic metal hydrides as well as with quantum chemical calculations and very different from 1 H chemical shifts usually found for hydroxide ions in similar materials. FTIR and Raman spectroscopy of different samples containing 1 H, 2 H, nat B, and 11 B combined with calculations unambiguously prove the absence of hydroxide ions and the sole incorporation of hydride ions into the borate. The orange‐red emission obtained by doping with Eu 2+ shows that the new compound class might be a promising host material for optical applications. Abstract : Enlighten me ! The unprecedented borate hydride (deuteride) Sr5 (BO3 )3 H (Sr5 (BO3 )3 D) is synthesized mechanochemically and its structure is determined by neutron diffraction. DFT calculations, NMR, IR, and Raman measurements unambiguously confirm the successful synthesis. An orange‐red phosphor is obtained upon doping with Eu 2+ .